2020
DOI: 10.1038/s41598-020-61373-9
|View full text |Cite
|
Sign up to set email alerts
|

Poly(Ethylene Oxide)-based Electrolyte for Solid-State-Lithium-Batteries with High Voltage Positive Electrodes: Evaluating the Role of Electrolyte Oxidation in Rapid Cell Failure

Abstract: polyethylene oxide (peo)-based solid polymer electrolytes (Spes) typically reveal a sudden failure in Li metal cells particularly with high energy density/voltage positive electrodes, e.g. Lini 0.6 Mn 0.2 co 0.2 o 2 (NMC622), which is visible in an arbitrary, time-and voltage independent, "voltage noise" during charge. A relation with SPE oxidation was evaluated, for validity reasons on different active materials in potentiodynamic and galvanostatic experiments. the results indicate an exponential current incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
200
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 195 publications
(247 citation statements)
references
References 53 publications
10
200
0
13
Order By: Relevance
“…[16] This could be evidenced by proper experiments that could eliminate the volta-noise, for example, an exchange of Li with graphite-based negative electrode or by an increase of SPE thickness, both rendering Li dendrites and their respective penetration difficult. [16] In agreement to these findings, the ease of Li denrite penetration through the SPE could be detected and even visualized in proper Li|SPE|Li cells. [20] A solution for overcoming this failure is the integration of the linear, rather soft PEO-based SPE, into a more mechanically robust semi interpenetrating network (s-IPN) (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[16] This could be evidenced by proper experiments that could eliminate the volta-noise, for example, an exchange of Li with graphite-based negative electrode or by an increase of SPE thickness, both rendering Li dendrites and their respective penetration difficult. [16] In agreement to these findings, the ease of Li denrite penetration through the SPE could be detected and even visualized in proper Li|SPE|Li cells. [20] A solution for overcoming this failure is the integration of the linear, rather soft PEO-based SPE, into a more mechanically robust semi interpenetrating network (s-IPN) (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 ] Indeed, a thorough investigation in our previous study confirmed a failure in an NMC622|SPE|Li cell, which is visible by an arbitrary appearance of “voltage noise,” typically emerging in initial cycles in random manner. [ 16 ] Micro‐shorts by Li dendrites, which is a morphology form of high surface area lithium, [ 17–19 ] were proven to be the origin of the this voltage noise failure; SPE oxidation as alternative reason for failure could be ruled out. [ 16 ] This could be evidenced by proper experiments that could eliminate the volta‐noise, for example, an exchange of Li with graphite‐based negative electrode or by an increase of SPE thickness, both rendering Li dendrites and their respective penetration difficult.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 The solid polyethylene oxide (PEO)-based PEs are among the essential materials for lithium-ion-polymer battery technology. 2 PEO is often being used as polymer matrix since it dissolves lithium salts based on the interaction between lithium ions and ether oxygens (EOs) in the polymer chains. 3 The technological relevance of PEO extends way beyond the energy storage area, and these polymers are also used for fuel cells and hybrid power sources supercapacitors.…”
Section: Introductionmentioning
confidence: 99%